2004
DOI: 10.1097/00006416-200401000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Depression in Adult Patients With Intravenous Patient-Controlled Analgesia

Abstract: Patient-controlled analgesia (PCA) has been widely implemented to provide better pain relief and increased patient satisfaction with relatively few side effects. However, patients using intravenous (i.v.) PCA are at increased risk for specific adverse effects, especially respiratory depression. A review of the literature from 1990 to present was done to identify the incidence and risk factors for respiratory depression and recommendations for care. Several studies have documented the incidence of respiratory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 26 publications
1
41
0
4
Order By: Relevance
“…This high degree of sensitivity will likely drive the technology to become pervasive in the post-anesthesia care unit, intensive care units and floors, where patients may be on patient controlled analgesia devices (PCAs). The latter potentially has the greatest safety impact, as a significant number of respiratory depression events occur in patients on PCAs [13]. According to Overdyk, respiratory failure after surgery is the "third most common cause patient safety-related adverse events affecting the Medicare population in U.S. hospitals, accounting for 113 events per 1,000 at-risk patient admissions, and (results) in death or anoxic brain injury in the majority of cases" [14].…”
Section: Resultsmentioning
confidence: 99%
“…This high degree of sensitivity will likely drive the technology to become pervasive in the post-anesthesia care unit, intensive care units and floors, where patients may be on patient controlled analgesia devices (PCAs). The latter potentially has the greatest safety impact, as a significant number of respiratory depression events occur in patients on PCAs [13]. According to Overdyk, respiratory failure after surgery is the "third most common cause patient safety-related adverse events affecting the Medicare population in U.S. hospitals, accounting for 113 events per 1,000 at-risk patient admissions, and (results) in death or anoxic brain injury in the majority of cases" [14].…”
Section: Resultsmentioning
confidence: 99%
“…ASA = American Society of Anesthesiologists physical status classification; BMI = body mass index; CAD = coronary artery disease; COPD = chronic obstructive pulmonary disease; CVD = cerebrovascular disease Dexmedetomidine and total knee arthroplasty 573 postoperative pain after total knee arthroplasty, which may place patients at increased risk of postoperative respiratory depression. 20 In a recent closed claims analysis of postoperative opioid-induced respiratory depression, Lee et al make note that 88% of closed claims involving postoperative opioid-induced respiratory depression events occurred within 24 hr of the surgical procedure. 21 As well, Chung et al found that, during the first postoperative night, increases in the central apnea index and obstructive apnea index in non-obstructive sleep apnea patients are correlated with the first 24-hr opioid requirement.…”
Section: Discussionmentioning
confidence: 99%
“…However, the basal administration increases the risk of respiratory depression without providing necessarily an additional analgesia patern [19].…”
Section: Pca: Principles and Pharmacological Aspectsmentioning
confidence: 99%